2006
DOI: 10.1158/0008-5472.can-06-0254
|View full text |Cite
|
Sign up to set email alerts
|

Ras-Associated Protein-1 Regulates Extracellular Signal-Regulated Kinase Activation and Migration in Melanoma Cells: Two Processes Important to Melanoma Tumorigenesis and Metastasis

Abstract: Melanoma is one of the most devastating malignances with a rising incidence and lack of effective treatments for advanced disease. Constitutive activation of the mitogen-activated protein kinase (MAPK) pathway and altered expression of A v B 3 integrin are critical for melanoma development and progression. Ras-associated protein-1 (Rap1), a Ras family member of the small GTPases, has emerged as a key mediator in these two important processes. In this study, we have shown Rap1 activation in cells derived from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
92
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 45 publications
5
92
2
Order By: Relevance
“…These reports suggested that the coordination of syndecan-2 and HS plays a role in cell migration; however, little is known about the key molecule that regulates such coordination. In this report, we demonstrate that Epac increases melanoma cell migration using two human melanoma cell lines: SK-Mel-2, which was derived from regional metastasis, and SK-Mel-24, which was derived from lymph node metastasis; both cell lines show potent migratory ability (16,38). We also demonstrated that syndecan-2 translocation and HS production are involved in Epac-induced cell migration.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These reports suggested that the coordination of syndecan-2 and HS plays a role in cell migration; however, little is known about the key molecule that regulates such coordination. In this report, we demonstrate that Epac increases melanoma cell migration using two human melanoma cell lines: SK-Mel-2, which was derived from regional metastasis, and SK-Mel-24, which was derived from lymph node metastasis; both cell lines show potent migratory ability (16,38). We also demonstrated that syndecan-2 translocation and HS production are involved in Epac-induced cell migration.…”
mentioning
confidence: 88%
“…Two isoforms of Epac, Epac1 and Epac2, were shown to mediate cAMP signaling to activate a small-molecular-weight G protein Rap1 and to regulate cellular functions, including secretion, Ca 2ϩ signaling, proliferation, and apoptosis (6). Several reports also indicate the involvement of Epac in regulating cell migration (16,28); however, the molecular mechanisms that lead to increased cell migration through Epacs remain unknown.…”
mentioning
confidence: 99%
“…We propose that efficient signaling of Rap1 to ERKs requires multiple events in addition to Rap1 activation, including phosphorylation by PKA and recruitment of KSR. This model may explain why constitutively active Rap1 mutants are poor activators of ERKs in the absence of PKA phosphorylation and may explain why constitutively active Rap1 mutants are rarely seen in human cancers (60). In this regard, it is interesting that the mitogenic actions of constitutively active Rap1 in a model of thyroid follicular cell growth required Rap1 phosphorylation (61).…”
Section: Ksr Is Required For B-raf To Bind Rap1 and Signal To Erks-mentioning
confidence: 99%
“…Further, Rap1 is also involved in the regulation of cell proliferation. When overexpressed, Rap1 induces oncogenic transformation in Swiss-3T3 cells (Altschuler and Ribeiro-Neto, 1998), and has been reported to be activated in metastatic mammary carcinomas, during melanoma tumorigenesis as well as metastasis (Hemmeryckx et al, 2001;Gao et al, 2006). Rap1 also appears to be involved in the process of thyroid mitogenesis and has been suggested to contribute to thyroid-stimulating hormone-stimulated thyroid tumorigenesis Hong et al, 2008).…”
Section: Introductionmentioning
confidence: 99%